Transcriptome-wide effects of inverted SINEs on gene expression and their impact on RNA polymerase II activity - Tajaddod, Mansoureh; Huber, Florian (Genome biology, 2016)
Short interspersed elements (SINEs) represent the most abundant group of non-long-terminal repeat transposable elements in mammalian genomes. In primates, Alu elements are the most prominent and homogenous representatives of SINEs. Due to their frequent insertion within or close to coding regions, SINEs have been suggested to play a crucial role during genome evolution. Moreover, Alu elements within mRNAs have also been reported to control gene expression at different levels.